2017
DOI: 10.1038/s41598-017-05950-5
|View full text |Cite
|
Sign up to set email alerts
|

Weakened IL-15 Production and Impaired mTOR Activation Alter Dendritic Epidermal T Cell Homeostasis in Diabetic Mice

Abstract: Diabetes is associated with impaired wound healing, which may be caused primarily by a deficiency in dendritic epidermal T cells (DETCs). In the epidermis, IL-15, IGF-1, and mTOR are known to regulate the maintenance of DETCs; however, it is unclear how these molecules may intersect to regulate DETC homeostasis in diabetes. Here, we show that the reduction of DETCs in the epidermis of diabetic mice is caused by altered homeostasis mediated by a reduction in IL-15 levels. Both impaired mTOR activation and reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 32 publications
(54 reference statements)
0
24
0
Order By: Relevance
“…Impaired mTOR signaling has been exhibited in diabetic epidermis. Others and our previous studies showed that mTOR signaling was deeply involved in regulating IGF-1 production in epidermis and DETCs ( 8 ). Now, we showed that rapamycin (an inhibitor of mTOR signaling) notably inhibited IGF-1 production in DETCs, which were freshly isolated from wound area by MACS, in the presence of rIL-15 plus anti-CD3 stimulation in vitro (Figure 4 B), suggesting that mTOR was involved in IL-15-mediated upregulation of IGF-1 production from DETCs.…”
Section: Resultsmentioning
confidence: 85%
See 4 more Smart Citations
“…Impaired mTOR signaling has been exhibited in diabetic epidermis. Others and our previous studies showed that mTOR signaling was deeply involved in regulating IGF-1 production in epidermis and DETCs ( 8 ). Now, we showed that rapamycin (an inhibitor of mTOR signaling) notably inhibited IGF-1 production in DETCs, which were freshly isolated from wound area by MACS, in the presence of rIL-15 plus anti-CD3 stimulation in vitro (Figure 4 B), suggesting that mTOR was involved in IL-15-mediated upregulation of IGF-1 production from DETCs.…”
Section: Resultsmentioning
confidence: 85%
“…IL-15 has been reported to play crucial roles in development and homeostasis of DETCs ( 19 , 32 ). Recently, we showed that reduction of epidermal IL-15 contributed to the altered homeostasis of DETCs in STZ-induced diabetic mice ( 8 ). In this study, we further revealed that impaired epidermal IL-15 production was a critical reason for insufficient activation and reduced IGF-1 production of DETCs in diabetic animals.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations